Three‐dimensional comparison of bone‐borne and tooth‐bone‐borne maxillary expansion in young adults with maxillary skeletal deficiency. (2nd July 2022) - Bazzani, Martina; Cevidanes, Lucia H. S.; Al Turkestani, Najla N.; Annarumma, Fabio; McMullen, Craig; Ruellas, Antonio C. O.; Massaro, Camila; Rego, Marcus V. N. N.; Yatabe, Marilia S.; Kim‐Berman, Hera; McNamara, James A.; Franchi, Lorenzo; et al.
Abstract: Objective: To compare the transverse dental and skeletal changes in patients treated with bone‐anchored palatal expander (bone‐borne, BB) compared to patients treated with tooth and bone‐anchored palatal expanders (tooth‐bone‐borne, TBB) using cone‐beam computer tomography (CBCT) and 3D image analysis. Methods: The sample comprised 30 patients with transverse maxillary discrepancy treated with two different types of appliances: bone‐borne (Group BB) and tooth‐bone‐borne (Group TBB) expanders. CBCT scans were acquired before (T1) and after completion of maxillary expansion (T2); the interval was 5.4 ± 3.4 and 6.2 ± 2.1 months between the T1 and the T2 scans of Group TBB (tooth‐bone‐borne) and Group BB (bone‐borne), respectively. Transverse, anteroposterior and vertical linear and angular three‐dimensional dentoskeletal changes were assessed after cranial base superimposition. Results: Both groups displayed marked transverse skeletal expansion with a greater ratio of skeletal to dental changes. Greater changes at the nasal cavity, zygoma and orbital levels were found in Group BB. A relatively parallel sutural opening in an anterior–posterior direction was observed in Group TBB; however, the Group BB presented a somewhat triangular (V‐shaped) opening of the suture that was wider anteriorly. Small downward‐forward displacements were observed in both groups. Asymmetric expansion occurred in approximately 50% of the patients in both groups. Conclusion: Greater skeletal vs dental expansion ratio and expansion of the circummaxillary regions were found in Group BB, the group in which a bone‐borne expander was used. Both groups presented skeletal and dental changes, with a similar amount of posterior palate expansion. Asymmetric expansion was observed in both groups.